Proper Treatment and Management of Postcardiotomy Refractory Vasospasm - Caleb R. Weissman; Stephane Leung Wai Sang (Case Reports in Cardiology)
We present here a unique case in which a 63-year-old man developed diffuse coronary vasospasm on postoperative day (POD) 1 following uneventful aortic valve replacement, replacement of ascending aorta, and coronary artery bypass. Subsequent emergent coronary angiogram demonstrated diffuse native coronary artery vasospasm that was only transiently responsive to intracardiac nitroglycerin, resulting in persistent cardiogenic shock and severe biventricular dysfunction. The patient was, thus, placed on femoral-femoral venoarterial (VA) extracorporeal membrane oxygenation (ECMO) with Impella support. This strategy allowed the weaning of vasopressors and enabled the resolution of the vasospasm. The patient was ultimately discharged on POD 17 without further complications. This case demonstrates our management strategy to provide life-saving support for patients facing postcardiac surgery refractory vasospasm.